Synthesis, Structure, and Catalytic Activity of A New Mn(II) Complex with 1,4-Phenylenediacetic Acid and 1,10-Phenanthroline - Li Hua Wang; Peng Fei Li (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
A new Mn(II) complex material has been synthesized by one-pot reaction of Mn(CH3COO)2·4H2O, 1,4-phenylenediacetic (H2L), 1,10-phenanthroline (phen), and NaOH in water/ethanol (v:v = 1:1) solution. The structure of Mn(II) complex was determined by elemental analysis, FTIR, and X-ray single-crystal diffraction analysis. The results reveal that Mn(II) complex was constructed by a monodentate 1,4-phenylenediacetate ligand, two phen ligands, a coordinated water molecule, 0.5 uncoordinated 1,4-phenylenediacetate ligand and six uncoordinated water molecules. The complex molecules form 1D chain structure by the π-π interaction of phen molecules. The catalytic activity of Mn(II) complex for coupling of benzaldehyde, phenylacetylene and piperidine in 1,4-dioxane has also been investigated and the maximum yield of propargylamine is up to 72.2 % after 12 h at 120 oC.